Molecular tools and bumble bees: revealing hidden details of ecology and evolution in a model system - S. Hollis Woodard; Jeffrey D. Lozier; David Goulson; Paul H. Williams; James P. Strange; Shalene Jha (Molecular Ecology, 2015)
Bumble bees are a longstanding model system for studies on behaviour, ecology and evolution, due to their well‐studied social lifestyle, invaluable role as wild and managed pollinators, and ubiquity and diversity across temperate ecosystems. Yet despite their importance, many aspects of bumble bee biology have remained enigmatic until the rise of the genetic and, more recently, genomic eras. Here, we review and synthesize new insights into the ecology, evolution and behaviour of bumble bees that have been gained using modern genetic and genomic techniques. Special emphasis is placed on four areas of bumble bee biology: the evolution of eusociality in this group, population‐level processes, large‐scale evolutionary relationships and patterns, and immunity and resistance to pesticides. We close with a prospective on the future of bumble bee genomics research, as this rapidly advancing field has the potential to further revolutionize our understanding of bumble bees, particularly in regard to adaptation and resilience. Worldwide, many bumble bee populations are in decline. As such, throughout the review, connections are drawn between new molecular insights into bumble bees and our understanding of the causal factors involved in their decline. Ongoing and potential applications to bumble bee management and conservation are also included to demonstrate how genetics‐ and genomics‐enabled research aids in the preservation of this threatened group.